Performance test of a hydrogen-powered solid oxide fuel cell system and its simulation for vehicle propulsion application - Kasar, Ibrahim; Fotouhi, Abbas; Nabavi, Seyed Ali (Elsevier, 2025)
Solid oxide fuel cells (SOFC) have not received enough attention as a power source in the transportation sector. However, with the development of the technology, its advantages over other types of fuel cells, such as fuel flexibility and high energy efficiency, have made SOFC an interesting option. The present study aims at simulation and experimentally validation of the performance of a hydrogen-powered SOFC in an automotive application. A 6 kW SOFC stack is tested, and its model is integrated into a series hybrid electric vehicle model. A fuzzy controller is designed to regulate the charging current between the battery and the SOFC in the vehicle model. Experimental tests are also conducted in a few cases on the SOFC based on the simulation results. The performance of the real SOFC stack is then analysed under dynamic loads to see how the desired current is provided in practice. The results demonstrate a good performance of the SOFC stack under variable load conditions.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; 7 Affordable and Clean Energy; Environmental Sciences; 33 Built environment and design; Solid oxide fuel cell; Hydrogen-powered; Vehicle propulsion; Fuzzy control